Kirk-Othmer Encyclopedia of Chemical Technology 2017
DOI: 10.1002/0471238961.1608151923050912.a01.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Flame Retardants

Abstract: Phosphorus flame retardants are a broad and expanding class of additive or reactive organic or inorganic compounds used to improve the fire safety of flammable materials such as plastics, textiles, wood, paper, and other flammable materials. In this article, their modes of action (vapor phase, condensed phase) and interactions are described, then specific classes of phosphorus flame retardants and significant compounds in each class are discussed. Attention is given to the chemistry and mode of use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…Acoustic cavitation is called the growth and collapse of bubbles under the influence of an ultrasonic field [ 89 ]. Ultrasonic waves propagate in a liquid medium, causing mechanical vibrations of the liquid.…”
Section: Cavitation Peeningmentioning
confidence: 99%
“…Acoustic cavitation is called the growth and collapse of bubbles under the influence of an ultrasonic field [ 89 ]. Ultrasonic waves propagate in a liquid medium, causing mechanical vibrations of the liquid.…”
Section: Cavitation Peeningmentioning
confidence: 99%
“…However, the addition of EG promoted a much milder decrease in mechanical properties in comparison to that of DMMP. Also, since EG is a carbon-based FR, it can be less harmful to the environment as its mechanism is mostly based on the formation of a carbonaceous char layer without the release of phosphorus-based compounds making EG potentially safer than DMMP. ,, Hence, based on the results, it could be noted that the WCO-based RPUF obtained comparable results with other materials presented in other studies based on the compression strength and flame retardancy, for instance. In this sense, Veronese et al proposed an interesting study to obtain a PU based on modified soybean and castor oils.…”
Section: Resultsmentioning
confidence: 59%
“…In contrast, WIB-IE3 had a higher CO production amount of 0.0533 kg/kg, which was related to the combustion of phosphoric acid in the vaporization stage (Kimmerle 1974). Trimethyl phosphate produced during the thermal decomposition of phosphoric acid reacts with oxygen first to interfere with methane-oxygen reaction, thereby slowing the progress of a fire (Weil and Levchik 2000). In addition, the proportion of incomplete combustion increased because it reduced the concentration of hydrogen atoms (Weil and Levchik 2000).…”
Section: Smoke Propertiesmentioning
confidence: 99%
“…Trimethyl phosphate produced during the thermal decomposition of phosphoric acid reacts with oxygen first to interfere with methane-oxygen reaction, thereby slowing the progress of a fire (Weil and Levchik 2000). In addition, the proportion of incomplete combustion increased because it reduced the concentration of hydrogen atoms (Weil and Levchik 2000). Further, the carbon monoxide yield (COY) curve of WIB-IE3 showed a similar trend to that of WIB-I and increased after s. Li (2003) and Niu et al (2014) reported that large amounts of CO are released during the process of burning combustion, in which carbide is turned into ash.…”
Section: Smoke Propertiesmentioning
confidence: 99%